THE SPATIAL DISTRIBUTION OF ABOVEGROUND BIOMASS IN TROPICAL FORESTS OF MEXICO - José Návar-Chaidez (Tropical and Subtropical Agroecosystems, 2011)
Biomass stocks and their spatial distribution remain poorly understood in tropical forests and reliable estimations are critical in the calculations of carbon stocks and fluxes. This report aims to estimate and contrast aboveground biomass (AGB) stocks in tropical forests of Mexico (classified as dry, moist and rainy) by employing three different evaluation techniques. The first method uses a simple mean biomass density value per each forest class multiplied by the area of each forest. The second approach improves the spatial resolution by classifiying forests per each region and a mean biomass density is multiplied by the area of each forest class. The third methodology calculates biomass stocks by developing an empirical model using mean annual precipitation as the independent variable and then applying the equation to the mean annual rainfall of each tropical forest times the area of the forest. Results showed that all three methods of AGB stock estimations are quite consistent since they have mean (confidence interval) values of 3.0 (0.69), 3.0 (0.30), and 2.25 (0.67) Pg estimated by first, second and third approaches, respectively. Deviations between evaluation methodologies did not surpass 0.45 Pg or 16% of the mean AGB stock. Using all three statistics, mean (confidence interval) aboveground biomass stocks for Mexican tropical forests is 2.77 (0.56) Pg. This statistic deviates by more than one order of magnitude when contrasting it with other six independent AGB estimates. However, the mean figure reported in this study or a mean AGB calculated across all estimation methods provides a dataset that is important for conducting carbon stocks and fluxes for Mexican tropical forests.